Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |
  • |

  1. Galileo Ferraris, “Sui cannocchiali con obiettivo composto di piu lenti a distanza le une dalle altre,” Atti R. Accad. Torino 16, 45 (1880).

1880 (1)

Galileo Ferraris, “Sui cannocchiali con obiettivo composto di piu lenti a distanza le une dalle altre,” Atti R. Accad. Torino 16, 45 (1880).

Ferraris, Galileo

Galileo Ferraris, “Sui cannocchiali con obiettivo composto di piu lenti a distanza le une dalle altre,” Atti R. Accad. Torino 16, 45 (1880).

Atti R. Accad. Torino (1)

Galileo Ferraris, “Sui cannocchiali con obiettivo composto di piu lenti a distanza le une dalle altre,” Atti R. Accad. Torino 16, 45 (1880).

Cited By

OSA participates in CrossRef's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Equations (46)

Equations on this page are rendered with MathJax. Learn more.

x = F M f = F H = object , or first , focal length x = F M f = F H = image , or second , focal length
Y = f / x = x / f ,
d 1 · 2 = F 1 F 2
x 2 = F 2 M 2 = F 2 M 1 = F 2 F 1 + F 1 M 1 = x 1 - d 1 · 2 .
x 2 = f 2 f 2 x 2 = f 2 f 2 x 1 - d 1 · 2 = f 2 f 2 f 1 f 1 / x 1 - d 1 · 2
x 2 = x 1 f 2 f 2 f 1 f 1 - x 1 · d 1 · 2 .
x 1 = x 2 f 1 f 1 f 2 f 2 + x 2 · d 1 · 2 .
Y 1 = f 1 / x 1 ,             Y 2 = x 2 / f 2
Y 1 · 2 = Y 1 · Y 2 = f 1 x 1 · x 2 f 2 .
Y 1 · 2 = f 2 f 2 + x 2 · d 1 · 2 f 1 f 2 ,
Y 1 · 2 = f 1 f 2 f 1 f 1 - x 1 · d 1 · 2 .
f 1 f 1 = x 1 · d 1 · 2 ,
F 1 F 1 · 2 = f 1 f 1 / d 1 · 2 .
x 2 = F 2 F 1 · 2 = - f 2 f 2 / d 1 · 2 .
x 1 = F 1 H 1 · 2 = f 1 f 1 / d 1 · 2 - f 1 f 2 / d 1 · 2 ,
x 2 = F 2 H 1 · 2 = - f 2 f 2 / d 1 · 2 + f 1 f 2 / d 1 · 2 .
f 1 · 2 = F 1 · 2 H 1 · 2 = F 1 · 2 F 1 + F 1 H 1 · 2 = - f 1 f 2 / d 1 · 2
f 1 · 2 = F 1 · 2 H 1 · 2 = F 1 · 2 F 2 + F 2 H 1 · 2 = f 1 f 2 / d 1 · 2 .
d i - 1 · i = F i - 1 F i .
D 1 · n = | d 1 · 2 f 2 0 - f 2 d 2 · 3 f 3 0 - f 3 d 3 · 4 · · · · · · · · · · · · · · · · 0 · d n - 2 · n - 1 f n - 1 0 - f n - 1 d n - 1 · n | .
D i · j = d j - 1 · j D i · j - 1 + f j - 1 f j - 1 D i · j - 2
D i · j = d i · i + 1 D i + i · j + f i + 1 f i + 1 D i + 2 · j .
D k · k = 1             and             D l · m = 0 ( l > m ) .
Y 1 · n = f n f n D 1 · n - 1 + x n D 1 · n f 1 f 2 f n
Y 1 · n = ( - 1 ) n f 1 f 2 f n f 1 f 1 D 2 · n - x 1 D 1 · n .
Y 1 · n - 1 = f n - 1 f n - 1 D 1 · n - 2 + x n - 1 D 1 · n - 1 f 1 f 2 f n - 1 .
x n - 1 = F n - 1 M n - 1 = F n - 1 F n + F n M n = d n - 1 · n + x n = d n - 1 · n + f n f n / x n = ( x n d n - 1 · n + f n f n ) / x n .
Y 1 · n = Y 1 · n - 1 Y n - 1 · n = Y 1 · n - 1 · ( x n / f n ) .
Y 1 · n = x n f n - 1 f n - 1 D 1 · n - 2 + ( x n d n - 1 · n + f n f n ) D 1 · n - 1 f 1 f 2 f n - 1 f n = f n f n D 1 · n - 1 + x n ( d n - 1 · n D 1 · n - 1 + f n - 1 f n - 1 D 1 · n - 2 ) f 1 f 2 f n
Y 1 · n = f n f n D 1 · n - 1 + x n · D 1 · n f 1 f 2 f n
x n - x 1 ,             d i · i + 1 d n - i · n - i + 1 , f i - f n - i + 1 ,             f i - f n - i + 1 .
F 1 F 1 · n = f 1 f 1 D 2 · n / D 1 · n ,
F n F 1 · n = - f n f n D 1 · n - 1 / D 1 · n .
f 1 · n = ( - 1 ) n - 1 ( f 1 f 2 f n / D 1 · n ) ,
f 1 · n = f 1 f 2 f n / D 1 · n .
D 2 · n = D 2 · j - 1 D 1 · n + [ i = 2 j - 1 ( - f i f i ) ] D j · n D 1 · j - 1 ,
Z = f 1 f 2 f n - 1 f n D 1 · n - 1 = f 1 D 2 · n ( - 1 ) n f 2 f 3 f n .
D 1 · 2 = d 1 · 2 = 2.0624 , D 1 · 3 = d 2 · 3 D 1 · 2 + f 2 f 2 = - 6.0756 , D 1 · 4 = d 3 · 4 D 1 · 3 + f 3 f 3 D 1 · 2 = 34.842 , D 1 · 5 = d 4 · 5 D 1 · 4 + f 4 f 4 D 1 · 3 = - 148.77 , D 1 · 6 = d 5 · 6 D 1 · 5 + f 5 f 5 D 1 · 4 = 277.16 , D 2 · 6 = D 2 · 3 D 1 · 6 + f 2 f 2 f 3 f 3 D 4 · 6 D 1 · 3 = d 2 · 3 D 1 · 6 + f 2 f 2 f 3 f 3 ( d 4 · 5 d 5 · 6 + f 5 f 5 ) D 1 · 3 = - 229.16 , f 1 · 6 = ( - 1 ) 5 f 1 f 2 f 6 D 1 · 6 = 17.052 mm , f 1 · 6 = f 1 f 2 f 6 D 1 · 6 = - 22.781 mm , F 6 F 1 · 6 = - f 6 f 6 D 1 · 5 D 1 · 6 = - 143.12 mm ,
F 1 F 1 · 6 = f 1 f 1 D 2 · 6 / D 1 · 6 = 4.771 mm ,
d k - 1 · k + 1 = F k - 1 F k + 1 = F k - 1 A k - 1 + A k - 1 A k + A k A k + 1 + A k + 1 F k + 1 = f k - 1 + A k - 1 A k + A k A k + 1 - f k + 1 ,
d k - 1 · k + 1 = ( n k + 1 / n k ) ( f k - 1 + A k - 1 A k ) + A k A k + 1 - f k + 1 ;
f 1 = 20 cm ;             f 1 = - 30 cm ;             f 3 = 170 / 7 cm ; f 3 = - 100 / 7 cm .
d 1 · 3 = ( 1.7 / 1.5 ) ( - 30 + 10 ) + 10 - 170 / 7 = - 776 / 21 ,
f 1.3 = - f 1 f 3 / d 1 · 3 = 1275 / 97 cm = - f 1.3
A 1 F 1.3 = A 1 F 1 + F 1 F 1.3 = - f 1 + f 1 f 1 / d 1 · 3 = - 155 / 97 cm
A 3 F 1.3 = A 3 F 3 + F 3 F 1.3 = - f 3 - f 3 f 3 / d 1 · 3 = 475 / 97 cm .